Dose‐dependent differential effects of thrombin in allergic bronchial asthma. (10th October 2013) - Miyake, Y.; D'Alessandro‐Gabazza, C. N.; Takagi, T.; Naito, M.; Hataji, O.; Nakahara, H.; Yuda, H.; Fujimoto, H.; Kobayashi, H.; Yasuma, T.; Toda, M.; Kobayashi, T.; et al.
Summary Background Apart from its role in the coagulation system, thrombin plays an important role in the inflammatory response through its protease‐activated receptors (PARs). However, the role of thrombin in the immune response is not clear. Objective To evaluate whether thrombin has a modulatory role in allergic bronchial asthma. Methods Bronchial asthma was induced in mice by intraperitoneal sensitization and inhalation challenge with ovalbumin. Thrombin or its inhibitors were administered by inhalation before each allergen challenge. Results Mice with low but sustained coagulation activation had reduced allergic inflammation, and allergic asthma was inhibited by low doses of thrombin but worsened by high doses. Allergic asthma was worsened by antithrombin, argatroban, hirudin, and anti‐thrombomodulin antibody. Mice with a higher level of an inhibitor of both thrombin and activated protein C had worse disease. Heterozygous PAR‐1 mice had less allergic inflammation, but PAR‐1 agonist worsened it. Allergic bronchial inflammation was worsened in mice that received adoptive transfer of PAR‐1 agonist‐treated Th2 cells as compared with controls. Low levels of thrombin suppressed the maturation and secretion of cytokines in dendritic cells, but high levels enhanced this. Conclusions The effects of thrombin on allergic asthma are dose‐dependent, with detrimental effects at high doses and protective effects at low doses. These data demonstrate that thrombin modulates the outcome in allergic bronchial asthma.